Benzodithiophenedione‐Based Conjugated Microporous Polymer Catalysts for Aerobic Oxidation Reactions Driven by Visible‐Light. Issue 8 (13th June 2019) - Zhang, He; Huang, Qiao; Zhang, Weijie; Pan, Chunyue; Wang, Jie; Ai, Chenxiang; Tang, Juntao; Yu, Guipeng
Abstract: Searching for catalysts that are cost‐effective, efficient, recyclable and capable of harvesting light for aerobic oxidation reactions remains a challenge for material scientists. Herein, we have designed and developed a task‐specified heterogeneous photocatalyst, which was built by a two‐step reaction starting from a commercially available compound named benzo[1, 2‐b:4, 5‐b′] dithiophene‐4, 8‐dione (BDD). Through the molecular engineering strategy integrating an electron‐output BDD, the obtained BDD‐based conjugated microporous polymer (CMP‐BDD) exhibits efficient visible light absorption due to the incorporation of a BDD moiety and an extended π‐conjugated structure. Remarkably, the CMP‐BDD showed an effective heterogeneous catalytic activity for typical oxidative organic transformations, such as selective oxidation of organic sulfides, and thiocyanation of imidazoheterocycles in the presence of light and oxygen. In addition, the CMP‐BDD exhibited good recyclability in the photocatalytic oxidation of thioanisole, which can be used for at least five times without substantial decline in photocatalytic activity, demonstrating its promising potential in industrial applications. Abstract : Reuse, recycle : A benzodithiophenedione‐based conjugated microporous polymer (CMP‐BDD) was synthesized which showed effective heterogeneous catalytic activity for typical oxidative organic transformations, such as selective oxidation of organic sulfides and thiocyanation of imidazoheterocycles in the presence of light and oxygen. In addition, the polymer exhibited good recyclability in the photocatalytic oxidation of thioanisole.